2011
DOI: 10.1088/2041-8205/741/1/l11
|View full text |Cite
|
Sign up to set email alerts
|

SECULAR EVOLUTION AND A NON-EVOLVING BLACK-HOLE-TO-GALAXY MASS RATIO IN THE LAST 7 Gyr

Abstract: We present new constraints on the ratio of black hole (BH) mass to total galaxy stellar mass at 0.3 < z < 0.9 for a sample of 32 type-1 active galactic nuclei (AGNs) from the XMM-COSMOS survey covering the range M BH ∼ 10 7.2−8.7 M ⊙ . Virial M BH estimates based on Hβ are available from the COSMOS Magellan/IMACS survey. We use high-resolution Hubble Space Telescope (HST) imaging to decompose the light of each type-1 AGN and host galaxy, and employ a specially-built mass-to-light ratio to estimate the stellar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
248
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(276 citation statements)
references
References 50 publications
27
248
1
Order By: Relevance
“…Lauer et al (2007) discussed how such a bias could affect studies of SMBH mass scaling relations using broad-line AGNs outside the local universe. In fact, recent studies have found tentative evidence for strong evolution in the scaling between M bh and host spheroid mass (e.g., Treu et al 2007;Jahnke et al 2009;Merloni et al 2010;Bennert et al 2011b; although see also Alexander et al 2008;Cisternas et al 2011). Our model, which assumes a constant scaling and scatter in the M bh -M * relation, may provide a simple explanation for such findings, although a full investigation is beyond the scope of this paper (see also Schulze & Wisotzki 2011;Volonteri & Stark 2011;Salviander & Shields 2013).…”
Section: The Nature Of the Agn Populationmentioning
confidence: 65%
“…Lauer et al (2007) discussed how such a bias could affect studies of SMBH mass scaling relations using broad-line AGNs outside the local universe. In fact, recent studies have found tentative evidence for strong evolution in the scaling between M bh and host spheroid mass (e.g., Treu et al 2007;Jahnke et al 2009;Merloni et al 2010;Bennert et al 2011b; although see also Alexander et al 2008;Cisternas et al 2011). Our model, which assumes a constant scaling and scatter in the M bh -M * relation, may provide a simple explanation for such findings, although a full investigation is beyond the scope of this paper (see also Schulze & Wisotzki 2011;Volonteri & Stark 2011;Salviander & Shields 2013).…”
Section: The Nature Of the Agn Populationmentioning
confidence: 65%
“…Given the importance of these BH scaling relations in our understanding of galaxy formation and evolution, there have been extensive observational efforts in the past decade both to refine the measurements of the local relations (e.g., Ferrarese & Merritt 2000;Gebhardt et al 2000a;Graham et al 2001Graham et al , 2011Tremaine et al 2002;Marconi & Hunt 2003;Häring and Rix 2004;Aller & Richstone 2007;Bentz et al 2009;Gültekin et al 2009;Kormendy & Ho 2013;McConnell & Ma 2013, and references therein) and to probe their possible redshift evolution (e.g., Treu et al 2004Treu et al , 2007Peng et al 2006aPeng et al , 2006bWoo et al 2006Woo et al , 2008Salviander et al 2007;Shen et al 2008b;Jahnke et al 2009;McLeod & Bechtold 2009;Bennert et al 2010;Decarli et al 2010;Merloni et al 2010;Cisternas et al 2011;Canalizo et al 2012;Hiner et al 2012;Targett et al 2012;Salviander & Shields 2013;Bongiorno et al 2014;Matsuoka et al 2014). Given the small angular size of the sphere of influence of the BH, so far all measurements beyond the local universe are based on broad-line quasar samples, where the BH mass can be estimated using the properties of the broad lines, instead of spatially resolved gas or stellar kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Other less important quenching mechanisms that affect central galaxies are mergers which could deplete the amount of cold gas available in the galaxy by triggering star formation (Mihos & Hernquist, 1996;Lambas et al, 2003;Woods et al, 2006;Bridge et al, 2007), secular processes such as morphological quenching (Kormendy & Kennicutt, 2004;Martig et al, 2009;Cisternas et al, 2011), and halo or mass quenching which ties quenching together with hot gas mass (Dekel & Birnboim, 2006;Cattaneo et al, 2006;Birnboim et al, 2007;Dekel et al, 2009;Gabor & Davé, 2015).…”
Section: Introductionmentioning
confidence: 99%